Implementasi Metode Tsukamoto Pada Sistem Pakar Diagnosa Kernikterus - Defiyuliyanti Bazikho; Efori Buulolo; Meryance V. Siagian (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Kernicterus is brain damage in infants due to high levels of bilirubin in the blood. Bilirubin is the cause of jaundice, and if left untreated, it can accumulate in the brain. The issue at hand is that the community, especially parents, still struggle to find a solution to determine the diagnosis of Kernicterus in a baby's body. Expert systems are advanced technology that can be used to address diagnostic problems with relevant accuracy. One of the expert system methods that can be employed for diagnosing diseases is Tsukamoto. Therefore, in this research, a expert system is built to obtain a Kernicterus diagnosis with relevant accuracy by implementing the Tsukamoto method to address the issues faced by patients. The results of this research show that testing the Tsukamoto method for diagnosing Kernicterus provides good accuracy. Hence, it can be concluded that implementing the Tsukamoto method in an expert system can be a solution to address the Kernicterus diagnosis problem